The Savings Behavior of Temporary and Permanent Migrants in Germany - Thomas K. Bauer; Mathias Sinning (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2005)
This paper examines the relative savings position of migrant households in West Germany, paying particular attention to differences between temporary and permanent migrants.Our findings reveal significant differences in the savings rates between foreign-born and German-born individuals. These differences disappear, however, for temporary migrants, if their remittances are taken into account. The results of a decomposition analysis indicate that differences in the savings rate between Germans and foreigners can mainly be attributed to differences in observable characteristics.We do not find strong evidence for an adjustment of the savings rate between immigrants and natives over time.
Keywords: F22; C24; E21; 330; Savings; Migration